2020
DOI: 10.1126/science.aay9501
|View full text |Cite
|
Sign up to set email alerts
|

Nitromethane as a nitrogen donor in Schmidt-type formation of amides and nitriles

Abstract: The Schmidt reaction has been an efficient and widely used synthetic approach to amides and nitriles since its discovery in 1923. However, its application often entails the use of volatile, potentially explosive, and highly toxic azide reagents. Here, we report a sequence whereby triflic anhydride and formic and acetic acids activate the bulk chemical nitromethane to serve as a nitrogen donor in place of azides in Schmidt-like reactions. This protocol further expands the substrate scope to alkynes and simple a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 111 publications
(39 reference statements)
2
74
0
Order By: Relevance
“…Reactions with substituted methylarenes were also investigated but they provided primary benzamides without C(aryl)-C(alkyl) bond cleavage (Scheme 15). 23 4. Cleavage of the C(aryl)-CH 3 bond via tandem oxidation/decarboxylative transformations Using amination/rearrangement strategies, great success has been achieved in the scission of the C(aryl)-C(alkyl) bond in ethylarenes, cumene, cyclohexylbenzenes, etc., but demethylative C(aryl)-CH 3 bond cleavage of inert methylarenes has been less reported.…”
Section: Monodentate Ligand Chelationassisted C(aryl)-c(sp 3 ) Bond Cmentioning
confidence: 99%
“…Reactions with substituted methylarenes were also investigated but they provided primary benzamides without C(aryl)-C(alkyl) bond cleavage (Scheme 15). 23 4. Cleavage of the C(aryl)-CH 3 bond via tandem oxidation/decarboxylative transformations Using amination/rearrangement strategies, great success has been achieved in the scission of the C(aryl)-C(alkyl) bond in ethylarenes, cumene, cyclohexylbenzenes, etc., but demethylative C(aryl)-CH 3 bond cleavage of inert methylarenes has been less reported.…”
Section: Monodentate Ligand Chelationassisted C(aryl)-c(sp 3 ) Bond Cmentioning
confidence: 99%
“…The amide bond (–CO–NH–) is an essential functional group in chemical synthesis, biology, and drug discovery Due to the prevalence of amides in both natural and unnatural materials, many synthetic protocols have been developed, The classical methods of preparation of secondary (2°) amides include the reaction of amines with carbonyl derivatives and hydroamination of alkynes Despite these developments, current trends on 2° amide syntheses are being focused on direct transamidation of unactivated amides & amidation of alkyl esters (entry A, Figure ), reaction between readily accessible phenyl thiocarbamates and Grignard reactants (entry B, Figure ), aerobic oxidative couplings of alcohols and amines and oxidation of benzylamines to benzamides under metal and metal‐free conditions Recently, Lei et al, reported an efficient Bu 4 NI‐catalyzed oxygen‐centered radical addition between acyl peroxides and isocyanides for the synthesis of 2° amides (entry C, Figure ) …”
Section: Figurementioning
confidence: 99%
“…Recently, various new N-containing molecules have been designed and synthesized, showing their utilities as photoelectronic materials 5 . Owing to the importance of N-containing molecules, the incorporation of nitrogen atoms into organic molecules through C–N bond formation is a major challenge in organic chemistry 6 .…”
Section: Introductionmentioning
confidence: 99%